Effect of projected band gap in the F -Cu system on the resonant charge transfer - Abas, Ahmed (University of Thi-Qar Journal of Science, 2019)
In this paper we study the effect of projected band gap on the resonant charge transfer when we use the grazing F- CUprojectile on the Cu surface with jellium potential. A wave-packet propagation method is used in the treatment of the resonant charge transfer process (RCT).Our study describe the long interaction time (low collision velocities)and we find the RCT efficiency is drastically reduced by the presence of the band gap. The important parameters are studied such that energy and width as a function to the distance between the surface and the projectile as well as the projected density of state at two different distance near (1 a.u.) and far from the surface (6 a.u.).